HUBUNGAN DINAMIKA KELOMPOKTANI SAGU TERHADAP KEMAMPUAN KELOMPOKTANI SAGU DI KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Ahmad Jihadul Ilmi Sukri; Rosnita Rosnita; Yulia Andriani (Fakultas Pertanian, Universitas Riau, 2021)
The purpose of this research are: Analyze the ability of sago farmers and analyze the relationship of sago group dynamics relation to the ability of sago group in Tebing Tinggi Barat district of Kepulauan Meranti Regency. This research uses survey method. This research was conducted in Tebing Tinggi Barat district of Kepulauan Meranti regency starting from April 2017 until January 2018. The sampling of 70 sago farmers was taken by purposive sampling. The data analysis used is Likert Scale analysis and Rank Spearman correlation. The results of this study indicate that: The level of dynamics of sago farmer group is classified as